Domestic Wastewater Management Program in East Bolaang Mongondow Regency - Kurniawan, Primasunu G.; Kairupan, Sisca B.; Tarore, Steven (Technium Social Sciences Journal, 2025)
This study aims to determine, analyze and describe the condition of infrastructure and the supporting and inhibiting factors of the domestic wastewater management program in East Bolaang Mongondow Regency. The research method used is qualitative research method. The results showed that first, Policy Standards and Objectives; The leaders in the Public Works and Spatial Planning Office (PUTR) already know the regulatory basis related to Domestic Wastewater Management. Then the people in Matabulu Village do not know the rules that apply to this program. And also in Matabulu Village, so far there has been no Standard Operational Procedure provided by the District Government to the Village Government. Even the achievement of the Program target is still not optimal. Second, Resources in Program Implementation; Program Beneficiaries are right on target, but the budget funds in this program are still lacking. Then there is participation provided by the Matabulu Village Community, such as providing land grants and labor assistance in the process of developing a Domestic Wastewater Management System (SPALD). And there are also parties who are responsible for the implementation of this program in East Bolaang Mongondow Regency, namely from the Community Self-Help Group (KSM). Third, Communication between Program Implementers; KSMs who carry out regular reporting to the Village Government and even to the PUTR Office. Furthermore, the socialization given to beneficiaries is only about the construction of septic tanks or the construction of this program, and there has been no further socialization related to this program in Matabulu Village. But it is also found that there is still a lack of providing solutions from implementers and beneficiaries related to existing obstacles.